Ghostgirl : lovesick - Hurley, Tonya (New York : Little, Brown and Company, 2010)
Charlotte has been given her first assignment after graduating from Dead Ed- the alternative high school for dead teens- she is to go back and help out a student from her previous life and her first love, Damen.
Angela Misa
Keywords: Future life -- Fiction; Friendship -- Fiction; Death -- Fiction; Ghosts -- Fiction; High schools -- Fiction; Schools -- Fiction